Aplikasi Pencarian Hotel di Kota Jakarta Berbasis Android dengan Metode Location Based Service (LBS) Menggunakan Android Studio - Siregar, Deo Rangga Sada; Koryanto, Lucky; Faizah, NM (Computer Journal, 2023)
The hotel is a resort for Jakarta and out of town people. Not all hotel locations are known to the public. Both in Jakarta city and out of city. This is due to the lack of information about hotels in Depok City. In order to be able to quickly provide information that can be used anytime, anywhere, it is necessary to advance and develop the times, such as the use of today's technology. B. Using an Android-based smartphone application to help a member of the public find a location and find a route to his Hotel of interest. Jakarta city. The waterfall process model is adopted as a research method. The hotel search application implementation uses JavaScript programming using Android Studio, location-based services, and maps sourced from the Google Maps API. The results of the survey are provided in the form of an Android-based hotel locator application in Jakarta city, allowing residents inside and outside Jakarta to find information about hotels and easily route from the user's location to the desired hotel in Jakarta. You will be able to obtain Cities with the help of GPS.